ESTIMATION OF EFFECTIVE SWATH ANGLE FOR MULTIBEAM ECHOSOUNDER NORBIT iWBMS - Algifari (15114086), Alif
Multibeam echosounder (MBES) with more modern system has larger swath angle and produces hundreds of beams. However, a hydrographic surveyor must still consider that the beam far from the nadir will produce a depth value with a greater error than the beam around the nadir. As a result, bathymetry data that acquired in the field is likely to have effective swath angle (usable) that meet vertical uncertainty tolerance IHO SP-44 5th edition which is smaller than the swath angle in the specifications. This study was conducted to determine the size of MBESÃ‚Â’s effective swath angle to be used as a consideration in determining the design parameters for the implementation of bathymetric surveys and determining the data that can be used in post-processing, in order to guarantee acquisition data meet depth accuracy specifications. The study was conducted using bathymetry data obtained from the acquisition using Norbit iWBMS Multibeam Echosounder System with operating mode 140o swath angle and 100% coverage in Pramuka Island. The bathymetric survey results giving data depth 5.33 m - 35.44 m and show a fairly varied topographic seabed shape. Effective swath angle estimation is done using beam-wise statistics method to determine maximum beam angles which mean depth errors meet order 1a and special order of IHO SP-44 (2008) standard. The results showed the estimated value of the effective swath angle Norbit iWBMS MBES was 140o for order 1a classification and 113.6o for special order classification. The application of effective swath angle parameters is considered to be able to improve the accuracy of the processing results and useful as input in making plans for conducting bathymetry surveys to ensure depth data accuracy meets surveys specifications and deliverables.